The effect of internet trust and social influence towards willingness to purchase online in Labuan, Malaysia - Alfhian Jeffri Chin; Syed Azizi Wafa Syed Khalid Wafa; Ai-Yee Ooi (Canadian Center of Science and Education, 2009)
This study is an empirical research one-commerce that examines the willingness of consumers to purchase online. The study focuses on two influential components that mediate the relationship between online shoppers and online vendors, namely, trust in the Internet structure and social influence. By using a convenience sample size of 115 from government servants and employees of private sectors residing in the Federal Territory Labuan who are computer literate, have access to Internet, and who possess credit card(s), this study aims to examine the relationship between the two variables of trust in the Internet structure and susceptibility to social influence on their willingness as consumers to purchase online. The findings show that trust in the Internet structure and susceptibility to social influence are significantly related to willingness to purchase online. However, hierarchical linear regression analysis had provided insignificant influence between trust in the Internet structure and willingness to purchase online with social influence as a moderator.